BEAMFORMING ANTENNA FOR 802.11AD/AY NETWORKS IN 60 GHZ - Hartmam Basaistegui, Raúl Hans; González Nappa, Mauricio; González Rivero, Juan Pablo; Rodríguez Díaz, Benigno (Telemática, 2023)
The ever-increasing traffic demands of wireless networks and the saturation of the lower bands of the radio spectrum have led the industry to adopt the use of ever-higher frequency bands. One of those bands is the 60 GHz band that has been incorporated into the Wi-Fi network standards within the IEEE 802.11 group in the past decade. In this work, the design of an antenna for use with beamforming techniques in the 60 GHz band is presented. The operating standards in the band are reviewed, from which requirements and criteria for the design are obtained. Simulations are performed and compared with the theoretical design, making adjustments and improvements to the original design. Techniques are applied to reduce secondary lobes, and the antenna is evaluated with multi-user transmission techniques to increase spectral efficiency.